CONSTRAINTS FACED IN ORGANIC RICE (Oryza sativa L.) FARMING AND STRATEGIES FOR PROMOTING ORGANIC RICE FARMING IN ANDAMAN AND NICOBAR ISLANDS - K. MADHU BABU, S. PRASANTH, I. SREENIVASA RAO and (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa var. indica) is the principal cereal crop of Andaman and Nicobar Islands. It is the principal staple item in the diet of Andaman and Nicobar populace and is cultivated on about 7,685 ha land. Annual rice production in A & N Islands is around 22000 tons with productivity of 2.98 t/ha while the extra requirement of island populace is around 60000 tons per annum (Gautam et al. 2013). Andaman and Nicobar Islands is situated in the tropical rainfall belt, agricultural operation in these islands are carried out under rainfed conditions and often integrated with livestock, aquaculture and vegetable garden. And it is one of the regions of the country suitable for organic rice production.